The attitudes of black businessmen and business women to the capabilities of black people in business - O'Brien, Carol Ann (My University, 1992)
In light of the skills shortages as well as the economic and political realities facing South Africa there:has been a growing realisation of the need to integrate Blacks and women into the mainstream of organisational life. Enabling 'Blacks and women to achieve their economic aspirations through non-discriminatory employee development has been recognised as crucial to long term economic growth in South Africa. In response to this reality a number of organisations have implemented affirmative action programmes. however, many South African organisations express dissatisfaction with the progress in Black advancement, despite considerable investment of resources in training and development initiatives. (Abbreviation abstract)
A research report submitted to the Faculty of Business Administration, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Management
Keywords: Executives, Black -- South Africa; Blacks -- Employment -- South Africa; Women executives -- South Africa; Women -- Employment -- South Africa; Discrimination in employment -- South Africa